Effectiveness of adolescent health education among secondary and senior secondary school girls in rural Bangalore - Kishor, Dharini; Madaiah, Madhusudan; Munipapanna, Santhosh; Sonnappa, Suresha Doddasabbenahalli (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescence is a phase of transition from childhood to adulthood. It is during this period that the adolescents acquire sexual and reproductive maturity. Health education given to adolescent girls helps build their knowledge, motivates them to improve and maintain their health, prevent diseases and reduce risky behaviors among them hence the study was done to assess the effectiveness of health education among rural adolescent girls. Methods: An educational interventional study was carried out among adolescent girls in one secondary and one senior secondary school in Hoskote, rural Bangalore. Initial survey was done to assess the baseline knowledge regarding adolescent health issues using semi structured, self-administered questionnaire. Health educational sessions were conducted using audio-visual aids such as slide presentations, charts, posters and handouts. The education was followed by an interactive session with the students to clarify doubts and the impact of intervention was assessed. Results: The study comprised of 150 students (75 secondary and 75 senior secondary school girls). It was found that overall general knowledge regarding adolescent changes, menstruation and menstrual hygiene, pregnancy, contraception and sexually transmitted infections including HIV/AIDS was poor among the study participants. Following educational session statistically significant improvement was observed among the students as detected by improved correct response rates. Conclusions: Study successfully proved that adolescent health education was effective in improving the knowledge among adolescent girls in rural area.